Chasing Ernst L Wynder: 40 years of Philip Morris' efforts to influence a leading scientist. Issue 8 (25th July 2003) - Fields, N; Chapman, S
Abstract : Study objective: To highlight strategies used by the Philip Morris tobacco company to try to manipulate the eminent scientist, Dr Ernst Wynder between 1955 and 1995. Methods: Systematic keyword and opportunistic searching of www.pmdocs.com for formerly internal tobacco industry documents concerning Philip Morris executives and Wynder. Available materials included reports, budget reviews, and correspondence. Main results: The emergence of smoking as a priority issue on the American public health agenda can be largely attributed to Wynder's research and publicity efforts. Philip Morris viewed Wynder as a prestigious scientist whose commitment to the pursuit of reduced harm cigarettes could lend legitimacy to its desire to position itself as a responsible company intent on addressing consumer concerns. Philip Morris courted Wynder with large equipment loans and grants for more than 30 years, and used its public relations agency to sanitise press releases to remove material unacceptable to the company. Wynder consistently failed to acknowledge industry support while routinely acknowledging other funding from the National Cancer Institute and the American Cancer Society. In retrospect, Wynder realised the insidious effect of tobacco industry research support but failed to acknowledge this may have applied to his own association with the industry. Conclusions: Industry documents reveal a deliberate attempt by Philip Morris to pursue and manipulate Dr Wynder to legitimise their company positions.